산업연관분석을 이용한 식품산업의 성장과 구조 변화 요인분석 - 김철민 (한국농촌경제연구원, 2003)
An Input-Output Analysis of Output Growth and Structural Change in the Korean Food Industry This paper examines the sources of output growth and structural changes in the Korean food industry over 1985-1995 using a decomposition method within the input output (IO) framework. This paper uses the linked input-output tables for 1985-1990-1995, as released by the Bank of Korea. These tables are deflated at 1995 constant prices. Basic 355 sectors categorized by the Bank of Korea were aggregated to 45 sectors to express food industry sectors well. The Bank of Korea is making I/O tables separating domestic transaction table and import transaction table. Therefore, a full import matrix is available. In this study the Korean food industry is categorized by 6 farm product sectors, 9 processed food sectors, and 5 non-food agricultural processing sectors. Other sectors as like farm input, manufacturing, and service sectors, are 25 sectors. The decomposition was applied to the 45 aggregation sectors for three different periods: 1985-1990, 1990-1995 and 1985-1995. The modeling was run on the aggregated classifications of 45-sector levels. Growth and structural changes were examined in terms of how changes in a sector's output can be apportioned between changes in (1) the effect of changes in domestic final consumption demand, (2) the effect of changes in domestic final investment demand, (3) the effect of changes in domestic final stock (4) the effect of import substitution in domestic final consumption demand, (5) the effect of import substitution in domestic final investment demand, (6) the effect of import substitution in domestic final stock (7) the effect of export demand, (8) the effect of import substitution of intermediate goods, (9) the effect of changes in input-output coefficients. The results indicate that growth of Korean food industry was dependent upon domestic demand, while growth of food industry is very low compared to overall industry. Overall, domestic demand expansion was the major factor raising output in the total processed food and nonfood agricultural processing industries. Researcher: Kim Chul-Min E-mail address: cmkim@krei.re.kr
Keywords: 산업연관분석; 식품산업